A Self-Adaptive QoS Guarantee Scheme for Multimedia Sensor Networks. (7th November 2010) - Sun, Yan; Ma, Huadong; Liu, Liang
Abstract : In multimedia sensor networks, there may exist simultaneously two streams: end-to-end stream and event-to-sink stream. It brings a new set of challenges for QoS guarantees in multimedia transmission. In this paper, we first present a self-adaptive QoS guarantee scheme based on two-layer feedback. In transport layer, we partition network into 10 typical states and design a transport protocol, which makes the state transition to the optimal one. Moreover, we design a revenue structure of media stream to describe the relation between QoS and multimedia capturing approaches in the application layer, thus evaluating the optimal scheme of capturing multimedia according to multimedia packet generation ratio calculated by transport layer. A series of simulation experiments using NS2 are performed to demonstrate the effectiveness of our proposed scheme.